PENGARUH LAYANAN BIMBINGAN KELOMPOK TEKNIK ROLE PLAYING TERHADAP REGULASI EMOSIONAL SISWA MTs AL-WASHLIYAH JATI REJO - Aulia, Nurika; Ika Sandra Dewi; Dina Hidayati Hutasuhut; Khairina Ulfa Syaimi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Emotion is a person's reaction to a situation. Emotions can be pleasant feelings such as joy, happiness, love and laughter. A person who has good emotional regulation can behave positively and benefit themselves and others. This study aims to determine the effect of group guidance using role playing techniques on the emotional regulation of students at MTs Al-Washliyah Jati Rejo. The method used in this study is pre-experimental research. The research design uses one group design pretest and posttest, namely the existence of a group that is given treatment preceded (pretest) before treatment and (posttest) after treatment. The population in this study were all class VIII MTs as many as 30 students. The researcher will use 10 students as research samples taken based on the results of the questionnaire that has been given and based on certain criteria. The instrument used in this study is a questionnaire. The data obtained are then calculated using statistical assessment. So that the results of the calculated t value are greater than the t table, namely (5.626> 2.262) indicating that the relationship between the two variables is positive. The significance value of 0.00 is smaller than the significance level of 0.05 (0.00 < 0.05), which indicates that the research hypothesis is accepted. Thus, the Role Playing Technique Group Guidance Service on Students' Emotional Regulation is proven.